Paedophilia and sexual crimes against children in Malaysia - Mohamad Yunus, Mohamad Ismail; Mohamad Hanifa, Shamshina; Abdul Rahman, Muhammad Ikhbal (Thomas Reuters Malaysia Sdn. Bhd., 2016)
One of Britain's worst paedophiles, who posted on the so-called “dark web” as he abused up to 200 Malaysian children, has been handed 22 life sentences. Briton Richard Huckle (born 14 May 1986) is a convicted sex offender of Paedophilia. He was arrested by Britain's National Crime Agency (NCA) after a tip-off from Australian Police and convicted of 71 counts of serious sexual crimes against children while posing as a teacher, photographer, and devout Christian in Malaysia. Huckle has been described as Britain's worst ever paedophile by both the media and the prosecution team, despite only being 28 years old at the time of his arrest, and on 6 June 2016, he was given 22 life sentences with a minimum prison term of 25 years before being eligible to apply for parole. How does the Malaysian Penal Code protect children against paedophilia and other sexual abuse? Does the law provide adequate protection to the children in Malaysia? Given the seriousness of child sexual crimes in Malaysia, and the growing public concern about this area of offence, law enforcement agencies need a committed and coordinated approach in detecting and countering paedophilia. Thus, the government recently established a proactive, intelligence-driven investigative task force called Sexual Crimes Against Children under the Prime Minister Department, which is to introduce the most effective law enforcement against paedophilia etc. By establishing the specialist task force in this way, offenders are likely to be detected, traced, identified and apprehended far earlier, with less resource, than with the traditional complaints-based approach.